Beyond the Acronym: Interlacing STEAM, Special Education, and Guiding Inquiry - Dignam, Christopher; Sexton, Rosemary; Munoz, Xochitl (International Journal on Studies in Education, 2025)
Interlacing STEAM and special education fosters inclusive, adaptive learning environments for special needs learners that support interdisciplinary and transdisciplinary instruction. The interwoven nature of STEAM enhances engagement, accessibility, and problem-solving for all learners, including students with disabilities. Constructivist methodologies, inquiry-based learning, and multimodal instruction ensure that STEAM extends beyond content knowledge to cultivate critical thinking, creativity, and self-efficacy. Assistive technologies, child-computer interactions, and digital fabrication provide pathways for diverse learners to participate in meaningful, inquiry-driven learning experiences. Intentional scaffolding supports students with varied cognitive and physical abilities, reinforcing engagement and accessibility. Professional erudition serves as a model for enhancing teacher capacity, combining targeted professional development with sustained, site-based professional learning. Findings indicate that STEAM education, when interlaced with special education, creates a responsive learning framework that empowers all students, strengthens interdisciplinary collaboration, and fosters accessibility. Recognizing STEAM and special education as interconnected rather than disparate disciplines ensures that learning remains dynamic, inquiry-driven, and inclusive for all students.